Development and validation of informed consent for blood transfusion questionnaire - Mohd Hilmi Senin; Mastura Mohd Sopian; Bakiah Shaharuddin; Muhammad Jaffri Mohd Nasir (Asian Journal of Transfusion Science)
INTRODUCTION: Blood transfusion warrants written informed consent from the patient. However, patients have poor knowledge regarding blood transfusions as evidenced by nonstandardized information retained by patients from the informed consent discussion. The problem stems from suboptimal patient knowledge on the elements of informed consent. This study describes the development and validation of a new questionnaire to assess the knowledge on informed consent for blood transfusion from the patients’ perspective. SUBJECTS AND METHODS: The development phase consisted of literature review, small group discussion, expert review meeting, content, and face validity. We evaluated the psychometric properties of Informed Consent for Blood Transfusion Questionnaire (ICBTQ) using reliability test and item response theory among a sample of 95 patients in Hospital Universiti Sains Malaysia. RESULTS: ICBTQ was formulated to include sociodemographic and knowledge sections. ICBTQ possessed excellent content validity. The face validity index (FVI) of clarity and comprehension were both 0.97. Thus, the universal FVI was 0.96. One item was added following the advice given by one of the content experts. ICBTQ had excellent face validity. For the validation phase, ICBTQ demonstrated an acceptable Cronbach’s Alpha value. One item was omitted in view of low corrected item-total correlation. In the item response theory (IRT) analysis, ICBTQ exhibited good difficulty and discriminatory indexes. Assessments of item-fit indicated that all items of the model were well-fitted. CONCLUSIONS: Based on the IRT and reliability analysis, the knowledge section of the ICBTQ was psychometrically valid to be used among patients.